The Relationship Between Mothers' Knowledge Level and Community Nurse Support with the Incidence of Stunting in Early Childhood - Rismanudin; Fitrah Ramadani; Ismiati Hi. yusuf; Fitria M radjak; Fani Fionita; Wahyuni (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2026)
Stunting is still a major health issue that influences children’s physical growth and development in Indonesia. Insufficient maternal knowledge and inadequate support from community nurses are factors that may increase the risk of stunting among young children. This study aimed to analyze the relationship between maternal knowledge and community nurse support with stunting incidence in early childhood. A quantitative cross-sectional design was applied involving 42 respondents selected through simple random sampling. Data collection used questionnaires and anthropometric measurements of height-for-age. Statistical analysis was performed using the Chi-Square test. The findings revealed that 38.1% of children were stunted, while 61.9% had normal growth status. Significant associations were identified between maternal knowledge and stunting occurrence, as well as between community nurse support and stunting incidence. Better maternal understanding and stronger nurse support were associated with lower stunting rates. Health education and community nursing services should therefore be strengthened to reduce stunting prevalence.